REFORMULASI HUKUM ISLAM DALAM PERSPEKTIF PANCASILA - Islamiyati, Islamiyati (Diponegoro Private Law Review, 2017)
Misunderstanding between Islamic law based on Islamic faith and Pancasila based on the agreement of the founders of the Indonesian nation, makes Islamic law unfit to appear in the realm of law science, so it is necessary to study analysis of the relationship between Islamic law with Pancasila and study efforts to reform Islamic law in the perspective of Pancasila. His analysis explains that between Pancasila and Islamic law, both of which go together in realizing the ideals and goals of national law. Pancasila is formed from the principle of unity, social justice, humanity, populist and Belief in the Almighty, all of which is a form of Islamic law practice Keywords: Reformulation, Islamic Law, Pancasila